2021
DOI: 10.1155/2021/1242481
|View full text |Cite
|
Sign up to set email alerts
|

Application of Multimode Health Education Combined with Humanistic Care in Pain Management of Patients with Femoral Fracture and Its Influence on VAS Score

Abstract: Objective. To explore the application of multimode health education combined with humanistic care in pain management of patients with femoral fracture and its influence on VAS score. Methods. A total of 120 patients with femoral fracture admitted in our hospital (May 2017–May 2021) were selected as the research objects. The patients who received routine health education were included into the routine group, and the patients who received multimode health education combined with humanistic care were included int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…This suggests that, with patients with low socioeconomic status, medical staff should focus more on humanistic care to reduce their negative emotions and relieve their pain intensity. A previous study suggested that health knowledge education could work in the short term, especially when patients were seriously ill or had severe pain ( 14 ). Additionally, Edwards et al confirmed that pharmacist educational interventions for cancer pain patients showed promise in reducing pain intensity ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that, with patients with low socioeconomic status, medical staff should focus more on humanistic care to reduce their negative emotions and relieve their pain intensity. A previous study suggested that health knowledge education could work in the short term, especially when patients were seriously ill or had severe pain ( 14 ). Additionally, Edwards et al confirmed that pharmacist educational interventions for cancer pain patients showed promise in reducing pain intensity ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Humanistic care involves a fundamental belief in the power of the care process to produce growth and change for people ( 13 ). Humanistic care can help patients to eliminate fear in multiple dimensions, improve their psychological threshold for pain, and become aware of pain control measures, thus enabling them to better cooperate with the treatment ( 14 ). Clinical pharmacists are professionals who are licensed pharmacists with specialized advanced training and provide patients with comprehensive drug management and related care in all medical areas ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Doctors, nurses, and patients should respect different values, such as compassion, multiculturalism, customization, and ethics, and push hospitals to integrate these values into their online health education initiatives [ 1 ]. Respecting human values means that hospitals follow ethical principles [ 11 ] and that health professionals consider patients’ expectations and beliefs [ 20 ]; moreover, these human values should also be integrated into the hospital’s medical protocols [ 21 ]. These human values must also be present within hospitals’ mobile apps.…”
Section: Discussionmentioning
confidence: 99%
“…), patients’ expectations, and legal frameworks to efficiently promote health education [ 20 ]. Promoting these human values positively contributes to making health education campaigns more efficient [ 21 ], especially when these campaigns aim to influence ethnic minorities with different cultural backgrounds [ 22 ]. Integrating human values into health education initiatives is essential for not only doctors, but also nurses.…”
Section: From Patients’ Education To Health Education Based On Mobile...mentioning
confidence: 99%
“…An emotional support also includes initiatives addressed to patients' relatives and friends (Troiseufs, 2020). This humanistic approach helps health organizations to switch the focus from diseases to patients, and this way reinforce these last ones' empowerment (Shi et al, 2021) Health education and mobile apps Doctors' and patients' skills in mobile literacy are essential for hospitals: without this knowledge, hospitals cannot implement health education campaigns (Yu et al, 2021). Promoting mobile apps as a health education tool means more than sharing medical information: hospitals need to use these technologies to change their internal processes and improve patients' satisfaction with medical services (Mateus-Coelho & Avila, 2021).…”
Section: A Multidisciplinary Approach For Health Educationmentioning
confidence: 99%